2017
DOI: 10.1111/jocn.13727
|View full text |Cite
|
Sign up to set email alerts
|

Accessing new understandings of trauma‐informed care with queer birthing women in a rural context

Abstract: Aims and objectives Participant narratives from a feminist and queer phenomenological study aim to broaden current understandings of trauma. Examining structural marginalisation within perinatal care relationships provides insights into the impact of dominant models of care on queer birthing women. More specifically, validation of queer experience as a key finding from the study offers trauma‐informed strategies that reconstruct formerly disempowering perinatal relationships. Background Heteronormativity gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…There were also no included studies involving parents with sexual diversity. However, a recent study of queer-identifying mothers highlights many of the issues identified in this review as important, with these women experiencing greater marginalisation within the maternity care system [77]. Olsen [78] found limited evidence of screening for child maltreatment during routine prenatal care, but that qualitative evidence suggested women were likely to be supportive of screening in prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…There were also no included studies involving parents with sexual diversity. However, a recent study of queer-identifying mothers highlights many of the issues identified in this review as important, with these women experiencing greater marginalisation within the maternity care system [77]. Olsen [78] found limited evidence of screening for child maltreatment during routine prenatal care, but that qualitative evidence suggested women were likely to be supportive of screening in prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“… Abbreviations: ANHSU, antenatal health service utilization; GDM, gestational diabetes mellitus; HIV, human immunodeficiency virus; SDOH, social determinants of health; QSEN, quality of safety education for nurses; Queer, member of the lesbian, gay, bisexual, queer, pansexual and two spirit (LGBQP2S) communities. 41 …”
Section: Resultsmentioning
confidence: 99%
“…We have a responsibility to advocate for inclusive forms and policies, as well as to actively discourage heteronormativity in a realm that is all too easily centred on just that. 43 Educators and training programs can create culture within an institution, as well as on a larger scale within communities. The identification of gaps in various stages of medical education is a necessary step to improve provision of care for all patients.…”
Section: Discussionmentioning
confidence: 99%